ANALISIS IMPLIKASI EKSEKUSI PENGANGKATAN SITA JAMINAN (CONSERVATOIR BESLAG) TERHADAP TANAH DAN BANGUNAN - Sibarani, Daniel Horas (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
This study examines the legal implications of the execution process for the lifting of conservatory seizure (conservatoir beslag) on land and buildings, based on the Ruling of the Head of the District Court No. 3 Pen.Eks/2024/PN Mad jo No. 3/Pdt.Eks/2023/PN Mad jo 4/Pdt.G/2023. The purpose of this research is to analyze the legal procedures and their impact on the ownership status of seized objects. This normative legal research adopts a qualitative approach, using document analysis and interviews conducted at the District Court and the Land Office of Madiun City. The results show that the lifting of conservatory seizure is not automatic and must be actively requested by the concerned party through a regulated procedure. The execution process was carried out in accordance with civil procedural law without significant obstacles. After the seizure is lifted, the land and building ownership certificates are restored to the original owner. This study emphasizes the importance of legal certainty and the protection of civil rights in the process of lifting conservatory seizure through court execution.